One Mental Shot AssessmenTherapy - OMeSA Un modello d'intervento pluralistico integrato blended change per diagnosi e cambiamento terapeutico in una (sola) seduta - Enrica Spalletta (Marp Edizioni, 2019)
Abstract The work illustrates a phase of pilot testing for a new model of blended-change (in presence and distant change) therapeutic intervention, based on a single session in which the fundamental principles of the Single-Session Therapy by Talmon are integrated with those of the Therapeutic Assessment by Finn and his colleagues. The OneMentalShotAssessmenTherapy, in line with the rules of the evidence - based integrated methods, is born with the purpose of offering the best conditions for a therapeutic process in an intensive setting, monitored with a constant check on the results, and is an excellent occasion for the personalization of the treatments.The intervention, tested at the moment on 10 adults (of which eight contacted singularly and two as a couple), is based on the realization of a definite protocol, from the telephonic welcome to the follow-up, divided into five phases in accordance with the gestalt contact cycle, implemented in relation to the pluralistic integrated approach. The cooperative use of the test's results, of self-evaluation questionnaires, and of guided reflection tools, allows to activate and enhance the patient's resources and to consider them as experts, basing the alliance not only on the empathy toward suffering, but also on the trust in their potential.